COVID-19 and Liver Damage - L. Yu. Ilchenko; I. G. Nikitin; I. G. Fedorov (Архивъ внутренней медицины, 2020)
An outbreak of unknown pneumonia, caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2), was reported in China at the end of December 2019. On February 11, 2020, the World Health Organization officially named SARS-CoV-2 infection COVID-19 (Coronavirus Disease 2019). The most common clinical manifestation of COVID-19 is pneumonia. However, with the spread of the COVID-19 pandemic and analysis of clinical data, symptoms that are not characteristic of “atypical” pneumonia have been identified in patients. Neurological symptoms, skin and eye damage, etc., are described. The extrapulmonary presence of SARS-CoV-2 was also detected in cholangiocytes. Virus-induced effects, systemic inflammation (“cytokine storm”), hypoxia, hypovolemia, hypotension in shock, drug-induced hepatotoxicity, etc., are considered possible factors of liver damage. In 14-53 % of COVID-19 patients, changes in biochemical parameters, which usually do not require drug therapy, can be recorded. Acute hepatitis is very rare. However, special attention should be given to COVID-19 patients at risk: after liver transplantation; receiving immunosuppressants and antiviral drugs; and in cases of decompensated cirrhosis, acute-on-chronic liver failure, and hepatocellular carcinoma. Constant data sharing and open access to research data, new technologies, and up-to-date guidelines are required.